Indeks Keanekaragaman Terumbu Karang Di Pulau Bintang Kecamatan Tolala Kabupaten Kolaka Utara Sulawesi Tenggara - Surahmat, Surahmat (Program Studi Pendidikan Biologi FKIP Uniiversitas Muhammadiyah Luwuk, 2023)
Bintang Island, which is located in Tolala District, North Kolaka Regency, is an island that has beautiful beaches and a fairly abundant coral reef population. The aim of thisresearch is to determine the coral reef diversity index. The type of research is quantitative descriptive which was carried out in December 2016. The location for taking sample images was determined on each side of the island with a total of 4 stations which will be installedvertically for a distance of 20 m, from the shoreline to the inside with the aim of being a route for laying a 2x2 plot. m in a zig-zag manner, totaling 10 plots. The research results were analyzed using the Shanon-Wiener formula. The results of the research found 32 species, namely Acropora humalis, A. palifera, A. caroliniana, A. donei, A. Formosa, A. gemmifera, A. gomezi, A. melliopora, A prostarata, A sarmentosa, A gracilis, Cycloseris costulata, Montipora aequituberculata, M. carpiocornis, M. danae, M. informis, M. tuberculosa, M. undata, Coeloseris mayeri, Cypahstrea decadie, Favie favus, F martima, F. abdita, Fungia concinna, Goniastrea minuta, Leptoseris papyraceae, L. scabra, L yabei, Pavona decussate, P. frondifera, Platygyra daedalea, and Turbinaria reniformis.. The Coral Reef DiversityIndex on Bintang Island at each Transect / Station respectively is I = 3.75, II = 3.10, III = 3.06, IV = 3.56, and overall the other transects have a diversity index of 3 .40 (H'>3), so the coral reef diversity index of Bintang Island, located in Tolala District, North Kolaka Regency, is considered high stability.